Development of Basin-scale PMP Estimation Method Using Grid-based Rain Search Method. (2016) - Kim, Youngkyu; Kim, Yeonsu; Yu, Wansik; Oh, Sungryul; Jung, Kwansue
Abstract: This study aims to develop a PMP estimation method in a basin-scale by considering both temporal and spatial characteristics and to compare the existing PMP estimation method with the developed method in this study. Since the movement of heavy rainfall is predictable like typhoons, DAD analysis method is usually utilized to storm centered DAD method and fixed areal DAD method. However, utilizing DAD in bigger basin area or longer rainfall duration induces more errors in estimation of average areal rainfall and thus reducing the accuracy of the results. Therefore, new DAD analysis method is necessary to improve the accuracy. In this study, by utilizing the new DAD analysis method, PMP was estimated through the processes of: firstly, converting point rainfall data to distributed areal rainfall data; secondly, a Grid-based rainfall search method was developed through the utilization of Average Point-tracking; and lastly, the PMP was calculated by considering moisture maximization. PMP estimation from using the new method was compared with the existing PMP as well as the areal maximum probable precipitation. As a result, even though the new estimate is lower than the exiting PMP, it was larger than the areal maximum probable precipitation (200-Year 48-Hour Areal Rainfall Frequency). Therefore, the estimated PMP can be utilized for the flood estimation.